PSYCOMETRIC PROPERTIES OF THE AUTHENTIC HAPPINESS SCALE (AHS) INDONESIAN VERSION WITH CONFIRMATORY FACTOR ANALYSIS AND RASCH MODEL - Wahyu Syahputra; Saiful Falah; Devie Yundianto (Al-Mubin, 2023)
This study aims to examine the psychometric properties of the Indonesian version of the authentic happiness scale (AHS), which includes an analysis of unidimensionality and item fit using the CFA and Rasch Model. Validity and reliability. This scale consists of authentic and fluctuating happiness consisting of 20 items, ten items each. The scale was administered to 112 educators as samples taken by purposive sampling. In the CFA unidimensionality test, ten items were eliminated to obtain a fit model, and ten items were re-examined and analyzed using the Rasch model. The above analysis results prove that AHS has good psychometric properties to be used in the Indonesian version